INNOVATIVE WAYS OF TEACHING RESEARCH FOR ESL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main purpose of teaching foreign language is communicative activity of students or working knowledge of foreign language. The task of the teacher is to reinforce the work of each student in the learning process and to come up with a situation for their creativity. There are many non-standard forms of work of the teacher activating attention and increasing the students’ interest in learning foreign languages.